Asian Yearbook of International Law, Volume 16 (2010) - Lee, Seokwoo; Eun Lee, Hee (Asian Yearbook of International Law, 2013)
The Yearbook aims to promote research, studies and writings in the field of international law in Asia, as well as to provide an intellectual platform for the discussion and dissemination of Asian views and practices on contemporary international legal issues. Readership: All interested in International Law and Asian Law.